O perfil da discriminaç\~ao no mercado de trabalho: Homens negros, mulheres brancas e mulheres negras - Sergei Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2000)
– This text decomposes the earnings differential between white men, on the one hand, and black men, white women, and black women, on the other. A difference in earnings may arise due to at least three causes: difference in human capital, different insertions in the labor market, or pure difference in wages. The text decomposes the differential of each category above into these three components. Both means and the full distributions of black males and black and white females are decomposed. The methodology is an extension of the Oaxaca decomposition for means. The results indicate that while the earnings differential for women is due exclusively to a pure wage differential, black males have lower earnings mainly due to differences in human capital, although they also suffer heavy wage and insertion discrimination. Black women suffer the pure wage differential of white women, plus the wage differential of black men, plus an insertion differential, plus a huge qualification differential (although it is smaller than that of black males).
Keywords: 330